Eastern Europe : Factors Underlying the Weakening Performance of Tax Revenues - Belanger, Gerard (IMF Working Papers; Working Paper ;, 1994)
The paper analyzes the decline of tax revenue/GDP ratios in transition economies of central and eastern Europe. The paper separates the effect on revenues of discretionary policy actions and finds that endogenous factors, notably the collapse of underlying profits and declining effective tax rates, were the main source of falling tax revenue/GDP ratios. Underlying factors are analyzed to provide a basis to discuss the outlook for tax revenues in coming years.